Ալզիի առաջին հիշատակությունները ասորեստանյան սեպագիր աղբյուրներում (Ք. ա. XIII դար) - Խուդանյան, Հարություն Հ. (ՀՀ ԳԱԱ Պատմության ինստիտուտ)
Страна Алзи расположенная в бассейне Верхнего Тигра Армянского нагорья и известной еще из хеттских клинописных текстов XIV в. до н. э., впервые упоминается в ассирийских клинописных надписях конца XIII в. до н. э. The land of Alzi situated in the Upper Tigris Basin of the Armenian Highland and still known from the Hittite cuneiform texts dated the 14th c. BC, is firstly mentioned in the Assyrian cuneiform inscriptions of the end of the 13th c. BC.
Keywords: Պատմություն; Սեպագրություն; Ասորական պատմագիտություն; Աղբյուրագիտություն